Etnobotani Arenga pinnata oleh Masyarakat Lokal Desa Bah Bolon Tongah Sumatera Utara dan Konservasinya - Marina Silalahi (University of Halu Oleo, 2020)
Arenga pinnata (AP) is a multifunctional plant used by various ethnic groups in Indonesia, including the Batak Ethnics in North Sumatra. Ethnobotany study is one way to find out the sustainable use of AP. This study aims to examine the use of AP and its conservation conservatives by the Batak ethnic community in the village of Bah Bolon Tongah, North Sumatra. This research was conducted with an ethnobotany approach through surveys and interviews with informants. Data analysis was carried out qualitatively to explain the utilization and conservation of AP. The Arenga pinnata by the local community in the Bah Bolon Tongah village is called pola, bagot, and tuak. The AP organs have different names is hodong (a compound leaf), halto (inflorescence), and ijuk (fibers produced by the stem). All parts of AP have been used such as leaves (roof, broom), stems (water pipes, buffalo bridles,